Characterization and Antifungal Activity of Limonoid Constituents Isolated from Meliaceae Plants Melia dubia, Aphanamixis polystachya, and Swietenia macrophylla against Plant Pathogenic Fungi In Vitro - Thanh Nguyen Tan; Hieu Tran Trung; Quang Le Dang; Hien Vu Thi; Hoang Dinh Vu; Tuan Nguyen Ngoc; Hoai Thu Thi Do; Thanh Huong Nguyen; Dang Ngoc Quang; Thang Tran Dinh (Journal of Chemistry)
The plants of Meliaceae are native to tropical and subtropical regions as the Americas, west India, Southeast Asia, and Southern China. Many species of the genera Khaya, Swietenia, Aphanamixis, and Melia in this family are known as medicinal plants and have biological activities such as antiviral, antimicrobial, antifeeding, insecticidal, and cytotoxic properties. The objectives of this research are to characterize and evaluate the bioactive limonoids from several plants of Meliaceae against phytopathogenic fungi. During the search of antifungal compounds from the plants of Meliaceae, the three methanol extracts of Melia dubia, Aphanamixis polystachya, and Swietenia macrophylla were found to suppress the mycelial growth of several phytopathogenic fungi. Nine limonoids isolated from M. dubia (1–2), A. polystachya (3–5), and S. macrophylla (6–9) were evaluated, for the first time, their antifungal effectiveness against nine phytopathogenic fungi Fusarium oxysporum, Magnaporthe oryzae, Sclerotium rolfsii, Rhizoctonia solani, Alternaria spp., and Botrytis cinerea, and three oomycetes Phytophthora species. Limonoids 2, 3, 6, and 8 displayed a remarkable broad-spectrum antifungal activity against all the test fungi. Sclerotium rolfsii was highly sensitive to the four limonoids with IC50 values ranging from 79.4 to 128.0 µg/mL. Notably, chisocheton compound G (3) isolated from A. polystachya and khayanolide B (8) isolated from S. macrophylla were the most potent antifungal limonoids and exhibited a dose-dependent activity against Phytophthora species. Compounds 2 and 9 displayed moderate activity against M. oryzae. Our study results demonstrated the discovery of antifungal and lead compounds from the group of limonoids for application in the control of fungal plant diseases.